MUHAMMAD AFIFUDIN DIMYATHI’S CONTRIBUTION IN THE DEVELOPMENT OF AL-QUR’AN SCIENCE AND TAFSIR IN INDONESIA - Aminullah, Reval Mhaulana; Kulsum, Ummi (Universitas Nurul Jadid, 2023)
Discussions about the history of Qur’an knowledge and tafsir development in Indonesia have not been prevalent recently. It is less lively than discussing Western ideas from Indonesian students studying in the West. However, at the same time, Middle Eastern alumni are now emerging who do not directly offset the spread of Western thought in this country. For this reason, this research discusses the analysis of the role and contribution of Muhammad Afifudin Dimyathi (Gus Awis) in the science of the Qur’an and Tafsir in Indonesia. Thus, this research aims to show and explain some of Gus Awis contributions to the history of the development of Qur’an science and Indonesian exegesis in modern times. This research uses descriptive qualitative methods with primary and secondary data sources. Primary sources were taken from books by Gus Awis, and secondary sources were taken from books, journal articles, and manuscripts related to the theme of this research. The results of this research state that Gus Awis contribution to the history of the development of the science of the Qur’an and tafsir in Indonesia, including (1) the conception of usūl al-tafsīr, (2) the collection of tafsir books from the 1st to the 15th centuries H, and ( 3) New colors in the interpretation of the Qur’an